Improving the performance of LTE technology by using MIMO and OFDM - Al-Janabi, H. D.; Vadia, Z. (Проблеми телекомунікацій, 2011)
In this paper we consider the ability to increase the LTE performance using MIMO systems and frequency diversity methods like as OFDMA and SC-FDMA. The effect of using the adaptive modulation in time and frequency domain by taking advantage MIMO and OFDMA and SC-FDMA in LTE technology is investigated.
Keywords: signal; channel; modulation; МІМО; LTE